Effects of Learning Agham Buddies (LAB) on the Conceptual Understanding of Matter among Fourth-Grade Pupils - Rogayan, Danilo V.; Macanas, Genalin A. (Jurnal Penelitian dan Pembelajaran IPA, 2024)
The current curriculum places a strong emphasis on learner-centered, activity-driven, and collaborative approaches to teaching and learning, particularly in the field of science. This action research aimed to investigate the impact of employing Learning Agham Buddies (LAB) on the conceptual understanding of matter among fourth-grade Science pupils. The study included 26 students from the experimental group (Grade IV Matikas) and 26 from the control group (Grade IV Mayumi) in a state-run elementary school in Zambales, Philippines. To assess the effectiveness of this intervention, both pre-tests and post-tests were administered before and after implementing LAB. The collected data included students' written work and performance tasks, which were analyzed to gauge improvements in their understanding of the topic. The results revealed a significant difference in conceptual understanding between the experimental and control groups, with LAB demonstrating a higher gain score (14.77) compared to traditional learning (11.81). This study recommends the adoption of LAB, a collaborative learning strategy, to enhance science students' conceptual understanding.